Effect of alcohol consumption on relapse outcomes among tuberculosis patients: A systematic review and meta-analysis - Weiangkham, Dao; Umnuaypornlert, Adinat; Saokaew, Surasak; Prommongkol, Samrerng; Ponmark, Jutamas (Frontiers in Public Health, 2022)
Abstract Tuberculosis (TB) is one of major public health issues in every country. Alcohol consumption is one of the reasons associated with severity symptoms and death among TB patients. The impact of alcohol use on TB relapse outcomes is still debatable. The aim of this study was to conduct a systematic review and meta-analysis (SR/MA) to find the link between alcohol use and TB relapse outcomes. Methods: Data collection was performed during December to March 2022; and was obtained from electronic databases including CINAHL, PubMed, and Scopus. The researcher carefully searched and reviewed all the relevant research concerning drinking alcohol and relapse outcomes among TB patients. A set of inclusion and exclusion criteria was used to assess research publications. The methodological quality of eligible publications was assessed using the Newcastle–Ottawa Scale. Random meta-analysis was used to determine odds ratios (ORs) with a 95% confidence interval (CIs). The funnel plot, Begg's test, and Egger's test were employed to investigate publication bias. Results: There were total of 2,113 studies found and reviewed; and numbers of eight publications were chosen for the analysis. It was found among TB patients with a moderate appearance of heterogeneity that drinking alcohol increases the probability of relapse (OR=3.64; 95% CI: 2.26–5.88, p<0.001) and mortality (OR=2.59; 95% CI: 1.67-2.87, p<0.001). The funnel plot, Begg's test, and Egger's test all revealed that there was no indication of publication bias. Conclusions: Relapses and mortality among tuberculosis patients are considerably increased by alcohol drinking. More research into the causality of this link between degree of alcohol use and the underlying processes is required.